2022
DOI: 10.3390/ma15031117
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Experimental Study on Reverse Helical Milling with the Gradual-Removal Reverse Edge Milling Cutter under Ultrasonic-Assisted Condition

Abstract: As a new machining method, ultrasonic-assisted bi-direction helical milling has obvious advantages in making holes on carbon fiber-reinforced plastics (CFRP). However, cutting edges of the flat-bottomed milling cutter are easy to wear, which may cause severe defects such as burrs and tears in the outlet of the hole. In order to improve the hole-making quality of CFRP, the gradual-removal reverse edge milling cutter was proposed and designed. The finite method models of reverse helical milling CFRP with the fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Based on the ultrasonic vibration amplitude and experimental cutting parameters in published Refs. [ 6 , 7 , 8 , 9 , 10 , 11 ], the cutting parameters for the experiment are planned and presented in Table 3 . Each cutting experiment has repeated ten times and the experimental cutting force are determined by averaging those cutting force value.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the ultrasonic vibration amplitude and experimental cutting parameters in published Refs. [ 6 , 7 , 8 , 9 , 10 , 11 ], the cutting parameters for the experiment are planned and presented in Table 3 . Each cutting experiment has repeated ten times and the experimental cutting force are determined by averaging those cutting force value.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies [ 11 , 12 ] showed that the ultrasonic vibration lowered the material strength by the activation of blocked dislocations. This effect is regarded as the thermal softening and acoustic softening effect.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren at al. [23] proposed a gradualremoval reverse edge milling cutter and demonstrated through simulation experiments that better accuracy can be achieved by using the gradual-removal reverse edge milling cutter in machining the inner wall of parts compared with the flat end milling cutter. Chen at al.…”
Section: Introductionmentioning
confidence: 99%